Spirometric and anthropometric improvements in response to elexacaftor/tezacaftor/ivacaftor depending on age and lung disease severity - Schütz, Katharina; Pallenberg, Sophia Theres; Kontsendorn, Julia; DeLuca, David; Sukdolak, Cinja; Minso, Rebecca; Büttner, Tina; Wetzke, Martin; Dopfer, Christian; Sauer-Heilborn, Annette; Ringshausen, Felix C.; Junge, Sibylle; et al. (Frontiers in Pharmacology, 2023)
Introduction: Triple combination CFTR-modulator therapy with elexacaftor/ tezacaftor/ ivacaftor (ETI) was introduced in 08/20 in Germany for people with CF (pwCF) >12 years (yrs.) of age and 06/21 for pwCF >6 yrs. of age. In this single-center study, we analyzed longitudinal data on percent predictive (pp)FEV1 and Body-Mass-Index (BMI) for 12 months (mo.) after initiation of ETI by linear mixed models and regression analyses to identify age- and severity-dependent determinants of response to ETI. Methods: We obtained data of 42 children >6-11 yrs., 41 adolescents ≥12-17 yrs. and 143 adults with spirometry and anthropometry prior to ETI and 3 and 12 mo. after ETI initiation. Data were stratified by age-group and further sub-divided into age-specific ppFEV1 impairment. To achieve this, the age strata were divided into three groups, each according to their baseline ppFEV1: lowest 25%, middle 50% and top 25% of ppFEV1. Results: Adolescents and children with more severe lung disease prior to ETI (within the lowest 25% of age specific ppFEV1) showed higher improvements in lung function compared to adults in this severity group (+18.5 vs. +7.5; p=0.002 after 3 mo. and +13.8 vs. +7.2; p=0.012 after 12 mo. of ETI therapy for >12-17yrs. and +19.8 vs. +7.5; p= 0.007 after 3 mo. for children >6-11 yrs.). In all age groups, participants with more severe lung disease showed higher BMI gains compared to those with medium or good lung function (within the middle 50% or top 25% of age specific ppFEV1). Regression analyses identified age as a predictive factor for FEV1 increase at 3 mo. after ETI initiation and age and ppFEV1 at ETI initiation as a predictive factor for FEV1 increase 12 mo. after ETI start. Discussion: We report initial data, which suggest that clinical response towards ETI depends on age and lung disease severity prior to ETI initiation, which argue for early initiation of ETI.